A 6-Year Update on the Diversity of Methicillin-Resistant Staphylococcus aureus Clones in Africa: A Systematic Review - Lawal, Opeyemi Uwangbaoje; Ayobami, Olaniyi; Abouelfetouh, Alaa; Mourabit, Nadira; Kaba, Mamadou; Egyir, Beverly; Abdulgader, Shima M.; Shittu, Adebayo Osagie (Frontiers in Microbiology, 2022)
Background: Methicillin-resistant Staphylococcus aureus (MRSA) is a leading cause of hospital-associated (HA) and community-associated (CA) infections globally. The multi-drug resistant nature of this pathogen and its capacity to cause outbreaks in hospital and community settings highlight the need for effective interventions, including its surveillance for prevention and control. This study provides an update on the clonal distribution of MRSA in Africa. Methods: A systematic review was conducted by screening for eligible English, French, and Arabic articles from November 2014 to December 2020, using six electronic databases (PubMed, EBSCOhost, Web of Science, Scopus, African Journals Online, and Google Scholar). Data were retrieved and analyzed according to the Preferred Reporting Items for Systematic Review and Meta-Analysis guidelines (registered at PROSPERO: CRD42021277238). Genotyping data was based primarily on multilocus sequence types (STs) and Staphylococcal Cassette Chromosome mec (SCCmec) types. We utilized the Phyloviz algorithm in the cluster analysis and categorization of the MRSA STs into various clonal complexes (CCs). Results: We identified 65 studies and 26 publications from 16 of 54 (30%) African countries that provided sufficient genotyping data. MRSA with diverse staphylococcal protein A (spa) and SCCmec types in CC5 and CC8 were reported across the continent. The ST5-IV [2B] and ST8-IV [2B] were dominant clones in Angola and the Democratic Republic of Congo (DRC), respectively. Also, ST88-IV [2B] was widely distributed across the continent, particularly in three Portuguese-speaking countries (Angola, Cape Verde, and São Tomé and Príncipe). The ST80-IV [2B] was described in Algeria and Egypt, while the HA-ST239/ST241-III [3A] was only identified in Egypt, Ghana, Kenya, and South Africa. ST152-MRSA was documented in the DRC, Kenya, Nigeria, and South Africa. Panton-Valentine leukocidin (PVL)-positive MRSA was observed in several CCs across the continent. The median prevalence of PVL-positive MRSA was 33% (ranged from 0% to 77%; n=15). Conclusions: We observed an increase in the distribution of ST1, ST22, and ST152, but a decline of ST239/241 in Africa. Data on MRSA clones in Africa is still limited. There is a need to strengthen genomic surveillance capacity based on a “One-Health” strategy to prevent and control MRSA in Africa.